(untitled) (Sains Humanika, 2024)
God can be perceived as an attachment figure (AF) who functions as a safe haven and secure base during distressful times. Nevertheless, stress levels might influence individuals’ attachment styles with God, which can in turn differentially affect their psychological well-being (PWB). study aimed to examine the mediating role of attachment to God in the relationship between stress and PWB among religious young adults. A mixed-methods design was utilized, whereby 118 participants completed a survey, and 4 participants were interviewed to obtain more in-depth insights about religious attachments. The quantitative results indicated that stress negatively predicted PWB and positively predicted insecure attachment to God, secure attachment to God positively predicted PWB, and insecure attachment to God negatively predicted PWB; however, stress did not predict secure attachment to God. Additionally, the relationship between stress and PWB was mediated by insecure attachment to God. For the qualitative aspect, , namely, a relationship with God provides security, religious attachments are hindrances in religious practices and sources of distress, religious insecurities create distress, and differences in ‘God’ conceptualizations. and the practical implication of considering religious attachments in therapy were also discussed.